Search found 1 match

Return to advanced search

Re: Mathematical Induction Question  TOPIC_SOLVED

P(n) is the nth summation in the series. n = 0 would be P(0). Each term is denoted as 2*(-7)^n. The first term is y(0) = 2*(-7)^0 = 2. Second term is y(1) = 2*(-7)^1 = -14. Third term is y(2) = 2*(-7)^2 = 98. Since there is just one term so far, the sequence (adding up of the terms from n= 0, 1, 2, ...
by SingingMommy
on Tue Nov 13, 2012 7:33 am
 
Forum: Discrete Math
Topic: Mathematical Induction Question
Replies: 4
Views: 3800

Return to advanced search